Resurrection of Salvia species (Lamiaceae) recently synonymized in Flora Mesoamericana - González-Gallegos, Jesús Guadalupe; Gama-Villanueva, Olga Jazmín (Phytotaxa, 2013)
Some species of Salvia were regarded as conspecific with other species of the genus in Flora Mesoamericana. Several of these changes are not justified and could eventually create misconceptions and confusion regarding the identification and distribution of these species, as well as the diversity exhibited by the genus. Therefore, in order to avoid the negative consequences of this synonymizing, updated and improved descriptions, a discussion of the diagnostic features, distribution maps and photographs of the taxa involved are provided here.